Analysis of the major headspace volatile components of beer by gas chromatography - Alvarez, Francisca A. (1976)
The major headspace volatile components of beer were analyzed by gas chromatography using a Varian Aerograph model A-600 B Hy-Fi equipped with a hydrogen flame detector. A 10 foot x 1/8 inch stainless steel column packed with 20% Carbowax 600 on Chromosorb W. was used to obtain the chromatograms. Freshly bottled beer were purchased on two different occasions. They were set aside for storage studies a room temperature and withdrawn at predetermined storage times. This study was undertaken for a duration of 24 weeks. The compounds isolated from the heaspace of beer were identified by comparing retention times of the unknown with those of standards. The volatiles were tentatively identified as acetaldehyde, acetone, ethyl acetate, ethanol, n-propanol, isobutyl alcohol and isoamyl alcohol. Two peaks were not identified because of lack of standards. Acetaldehyde, acetone, n-propanol, and an unidentified peak (#7) may have been present only in very small amounts. Percent concentrations of ethyl acetate, isobutyl alcohol an isoamyl alcohol were taken relative to ethanol. Fluctuations in percent relative concentration were noted on the first twelve weeks of storage but thee evened out thereafter. Physico-chemical properties showed fluctuations in values at the start of the storage study but thee likewise stabilized s the volatiles attained a stable value. No significant changes in the flavor and acceptability of beer during the 24 weeks storage period were observed by a taste panel composed of ten (10) male beer drinkers.
Mimeographed.
Thesis (M.S.)--University of the Philippines, Quezon City.
Keywords: Beer